The influence of the molecular weight of hyaluronic acid on the mangiferin release kinetics from the polymer matrix - P. P. Snetkov; R. O. Shaikenov; V. I. Klimshina; Yu. E. Generalova; S. N. Morozkina (Разработка и регистрация лекарственных средств, 2025)
Introduction. Currently, the use of natural biologically active agents (BAA) as effective antibacterial drugs for both external and internal use is becoming widespread. Polyphenol mangiferin, extracted from the leaves of the Mangifera indica plant, is the most attractive BAA. Despite high antimicrobial activity against gram-positive and gram-negative strains of bacteria, the use of mangiferin is limited by its low aqueous solubility. To increase solubility and, accordingly, bioavailability, various approaches are used, in particular, encapsulation in polymer and biopolymer matrices. One of the promising biopolymers for the encapsulation of biologically active substances is hyaluronic acid, which is completely biocompatible with the tissues of a living organism and is capable of complete biodegradation under the influence of enzymes (hyaluronidases).Aim. Study of the release kinetics of the biologically active agent (mangiferin) from a polymer matrix based on hyaluronic acid with different molecular weights.Materials and methods. Polymer films obtained by casting method from 1.5 wt.% forming solutions of hyaluronic acid with a molecular weight of 1.30 and 2.48 MDa with different contents of mangiferin were used as the objects of the study. The weight ratio of hyaluronic acid to mangiferin varied from 5 to 25. Released mangiferin was measured by UV/Vis spectrophotometry at a wavelength of 237 nm. A phosphate buffered saline with pH 7.4 was used as a model medium. The mangiferin release kinetic was assessed using various mathematical models.Results and discussion. Mangiferin release kinetic from a polymer matrix based on hyaluronic acid has a release sigmoidal pattern. The release mechanism has a complex nature of the Super Case II transport type, with the exception of a sample with a low content of mangiferin and hyaluronic acid with molecular weight equal to 1.3 MDa, for which an abnormal release pattern is detected (non-Fickian diffusion), due to the hydrophilic nature of hyaluronic acid, the rapid swelling of the polymer matrix, as well as a significant leading in the diffusion of mangiferin compared to the relaxation rate of the polymer. The most suitable model is the Weibull model, which describes the mangiferin release kinetics with greater accuracy compared to other mathematical models.Conclusion. The results obtained indicate the potential possibility of using the developed polymer films as biomedical materials for external use, which provide transdermal delivery of pharmaceutical agents. The authors of the study are planning to develop a methodology for prolonged and controlled release of a loaded biologically active agent, including by various cross-linking agents.